Epidemiology and psychology in handling the psycho-social problem Covid-19 - Saifullah Idris, Ramzi Murziqin,; Usman, Nasir; Tabrani ZA, Hayati, (Opción)
This article tries to touch on the most common types of infectious diseases in the world today, Covid-19, the cause of its spread, its control, and its development. The design of this study is a descriptive method with the form of qualitative research. The technique used in this method is library research, where all possible information and literary review that have relation to the study are collected and takes as the source of information. The results of the study show that it is difficult to avoid the complex relationship between humans and pathogenic microorganisms in the efforts of the authorities to develop programs for the control and prevention of infectious diseases.